Makna Ruang Publik Kedai Kopi Bagi Remaja Di Wilayah Solo - Rini Agustin, Eka; Nurhadi, Nurhadi; Galih Pudyastuti, Septina (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The existence of coffe shops since they first appeared until now has an increasing number of enthusiasts day by day. The lifestyle of consuming coffe in coffe shops has become normal in various circles, but not all teenagers who visit coffe shops are consumptive and hedonistic. They carry out various activities which are of course beneficial for them personally. Instantly, these various activities made the coffe shop a public space that was used by teenagers. This research aims to find out what activities teenagers do in coffe shops and what the meaning of coffe shops are doing assignments, completing work, refreshing and hanging out, endorsement, enjoying food and drinks, family gatherings, tourist visits, and me time. And for them, a coffe shop is meaningful as a source of inspiration, as a moodboster, individualistic and private, as a free space, and an interesting place. As a public space, coffe shops are an alternative choice for teenagers to freely express and act without having to think about anything.Kata kunci:Â  Kedai Kopi, Remaja, Ruang Publik